2017
DOI: 10.1002/ldr.2843
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil redistribution patterns with 137Cs measurements in a Mediterranean mountain catchment affected by land abandonment

Abstract: In Mediterranean mountainous environments, the removal of natural vegetation for developing agriculture increased the surface areas prone to erosion in the past centuries. In Southern PrePyrenees, the process was inverted during the middle of the 20th century. This work aims to assess how land use changes after widespread land abandonment affect soil redistribution. For this purpose, 137 Cs was used in a 23 km 2 catchment that was mostly cultivated at the beginning of the past century. After land abandonment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…In this study, no flat undisturbed sites that can 467 serve as typical reference sites were found, and reference sites were selected based on 137 accidental radionuclide emissions, their use in geomorphological studies provides an opportunity to 481 reconstruct soil redistribution due to soil erosion processes at larger scales (Chappell et al, 2011b;482 Meusburger et al, 2020). Although estimates of erosion rates at continental scales are debated (Fiener 483 and Auerswald, 2016;Panagos et al, 2015;Panagos et al, 2016), prediction of 137 Cs initial fallout at 484 kilometric scales offers the potential to increase our knowledge of soil erosion processes in catchments 485 through the use of the 137 Cs inventory technique and its upscaling (Lizaga et al, 2018). In general, the 486 spatial distribution of anthropogenic radionuclides in soils and their use as tracers of environmental 487 processes is of significant importance for Earth and atmospheric sciences (Bhandari, 1970;Everett et 488 al., 2008;Hirose, 2012;Igarashi et al, 2011;Jagercikova et al, 2017).…”
Section: Improving Spatial Predictions Through Additional Sampling 395 396mentioning
confidence: 99%
“…In this study, no flat undisturbed sites that can 467 serve as typical reference sites were found, and reference sites were selected based on 137 accidental radionuclide emissions, their use in geomorphological studies provides an opportunity to 481 reconstruct soil redistribution due to soil erosion processes at larger scales (Chappell et al, 2011b;482 Meusburger et al, 2020). Although estimates of erosion rates at continental scales are debated (Fiener 483 and Auerswald, 2016;Panagos et al, 2015;Panagos et al, 2016), prediction of 137 Cs initial fallout at 484 kilometric scales offers the potential to increase our knowledge of soil erosion processes in catchments 485 through the use of the 137 Cs inventory technique and its upscaling (Lizaga et al, 2018). In general, the 486 spatial distribution of anthropogenic radionuclides in soils and their use as tracers of environmental 487 processes is of significant importance for Earth and atmospheric sciences (Bhandari, 1970;Everett et 488 al., 2008;Hirose, 2012;Igarashi et al, 2011;Jagercikova et al, 2017).…”
Section: Improving Spatial Predictions Through Additional Sampling 395 396mentioning
confidence: 99%
“…The impact of water erosion on cultivated lands is one of the major threats to soil fertility, such as in the Mediterranean mountain region (Lizaga et al, 2018;Barreiro-Lostres et al, 2017;Navas et al, 2008;Lasanta et al, 2006). Land use conversion to cropland associated with a long history of human activity, had important effect on the intensity of soil erosion (Gaspar et al, 2019(Gaspar et al, , 2013Lizaga et al, 2017) and on the storage and stability of carbon in soils (Quijano et al, 2017(Quijano et al, , 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, studies reporting only theoretical descriptions of models or enhancements of single models, components, or parameters were not considered suitable for the analysis. Similarly, studies reporting on measurements only, e.g., the analysis of fallout radionuclides as indicators of erosion processes ( Lizaga et al, 2018 ; Mabit et al, 2019 ), were not taken into account.…”
Section: Discussionmentioning
confidence: 99%